Introduction to compassionate view intervention: A Buddhist counseling technique based on Mahāyāna Buddhist teachings - Lee, Kin Cheung (George) (Journal of spirituality in mental health, 2019)
Although the need for Buddhist chaplaincy has been increasing tremendously, very few counseling resources and interventions are tailored for Buddhist chaplains. Based on the compassion ideal in Mahāyāna Buddhism, this article introduces the compassionate view intervention (CVI) for Buddhist chaplaincy to support its provision of spiritual care for clients. CVI has three components: (1) integrating compassion in the therapeutic stance as a chaplain; (2) flourishing a compassionate mind in clients by discussing the concept of compassion and meditation, and; (3) applying compassionate view exercises. Detailed descriptions of CVI and a case example are provided to illustrate the practicality of application.